Medios de comunicación y opinión ciudadana - Morales Autheman, Diana Carolina (2019)
This study deals with the incidence of the content of the Ecuador TV channel in the opinion of young people between 25 and 30 years old, residing in the sector of Mucho, Lote. The third stage of the city of Guayaquil, started by analyzing the editorial line of the Middle, identifying the main news it issues, and based on that, analyzing the influence of these contents on the youth population. It was approached from a field study, combining qualitative and quantitative methods, where a group of 380 young people between 25 and 30 years of age were studied…….